“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction

Gendered impacts of the COVID-19 pandemic: A mixed-method study of teacher stress and work-life balance - Leo, Aaron; Holdsworth, Elizabeth A.; Wilcox, Kristen C.; Khan, Maria I.; Mola Ávila, José Antonio; Tobin, Jessie (Community, Work and Family, 2022)
There is a growing concern that the COVID-19 pandemic has had disproportionate impacts on women, especially those with children. Female educators, and, in particular, those with childcare responsibilities, have also reported higher levels of stress and work-life challenges as compared to their male counterparts. It is unclear exactly which factors are behind these disparities. However, while some have pointed to the gendered division of domestic labor as the main contributor, other pandemic-related and work-related stressors may be involved in female educators’ increased stress levels and work-life balance challenges. To address this question, this mixed-methods research draws on survey data gathered from 752 educators across New York State. Findings demonstrate that women reported higher levels of stress and work-life balance challenges than their male counterparts. While quantitative analyses indicated that gender disparities in work-life balance challenges were related to the higher stress women experienced from work and COVID-19 rather than childcare responsibilities, qualitative analyses of open-ended survey responses revealed that childcare duties were nonetheless an important factor impacting work-life balance challenges for both men and women. This article has significant implications for the teaching profession and adds broader insights into the gendered effects of the pandemic. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; covid-19; division sexuelle du travail; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; santé au travail; systèmes d'oppressions; thématiques; travail; états-unis

Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail